Primary non-continuous new daily persistent headache: Seven cases and proposed diagnostic criteria - Randolph W Evans (SAGE Publishing, 2021)
Primary new daily persistent headache (NDPH) is a rare disorder defined by the third edition of the International Headache Society (ICHD-3) as a continuous and unremitting headache. Non-continuous cases have been reported which do not fit any ICHD-3 criteria. Seven patients are presented who meet all ICHD-3 criteria except for being non-continuous from onset without treatment with a duration of 4 or more hours per day with only one headache per day. The average age of onset was 35.3 years, 57.1% female, and 71.4% had migraine-like features. No cases were unilateral and all cases were persistent without remission. These seven cases constitute a primary NDPH variant. Criteria are proposed for diagnosis similar to ICHD-3 for NDPH with the following change: "pain becoming daily within 24 hours of onset with a duration of 4 to 24 hours without acute or preventive medication or other treatment."